REHABILITATION OF ONCOGYNECOLOGIC PATIENTS. VIEW OF A PROBLEM - A. G. Solopova; Y. Y. Tabakman; L. E. Idrisova; A. M. Sdvizhkov (Акушерство, гинекология и репродукция, 2016)
The problem of rehabilitation of cancer patients continues to be actual. Development of methods of therapy of malignant tumors has improved the results of survival of patients. At the same time feature of the applied methods are numerous complications. The rehabilitation course is necessary for all oncological patients who received radical surgeries, radiation and medication therapy. The existing directions of the rehabilitation help to onсogyneсologic patients are limited to treatment of an oncopathology, prevention and treatment of climacteric disturbances, psychological assistance and, in some cases, physiotherapeutic procedures. It is expedient to create the system of the rehabilitation help to cancer patients allowing to provide consecutive stage-by-stage rehabilitation of patients according to individually developed program.